HMI SIMULATION OF BIOGAS HANDLING OF GAS ENGINE SYSTEM - Nugroho Adi Sasongko; Anton Rahmawan; Hartadhi Hartadhi; Arga Febriantoni; Winaldha Erza N.H.; M. Taufiqi Arrais; Agus Rochmansyah (Jurnal Energi dan Lingkungan (Enerlink), 2018)
Palm oil waste such as Palm Mill Effluent (POME) can endanger the environment, sincePOME stillcontains organic compounds with highCOD and BOD. To reduce COD and BOD level, POME needs tobe processed into environmentally friendly and useful products. One of the products is biogas, whichcan be used as fuel for gas engines to produce electricity. Biogas can be an alternative to diesel fuel.The results of the study indicatedthat the amount of biogas content from the new POME waste processcan be used to supply gas engines. It is necessary to optimize the design of the Human MachineInterface (HMI)ofthe biogas cleaning system such as bioscrubber, dehumidifier, and blower units,using instrumentation and control software called Virtual Instrument Engineering WorkbenchLaboratory (LabVIEW). LabVIEWis a system design platform and development environment for visualprogramming languages from National Instruments (NI), USA. Instrumentation and control systemsare designed for automation with graphic programming languages. The built-in interface helps simplifycomplex functions such as visualizing the control system in a large database and system-processingoptimization that has been designed.Kata kunci: biogas, gas engine, gas handling, labVIEW, POME (Palm Oil Mill Effluent)